Patterns and trends of hepatitis C virus infection in Jordan: an observational study - Abu-Dayyeh, Issa; Chemaitelly, Hiam; Ghunaim, Mohammad; Hasan, Thaer; Abdelnour, Amid; Abu-Raddad, Laith J. (Frontiers in Public Health, 2023)
Background: Hepatitis C virus (HCV) infection levels in Jordan remain uncertain. No HCV national population-based survey has ever been conducted in the country. To meet the World Health Organization's target of reducing HCV incidence to ≤5 per 100,000 people per year by 2030, it is essential to determine the infection levels, identify affected individuals and populations, and provide appropriate treatment using direct-acting antivirals to individuals carrying the virus. Methods: The study utilized the HCV testing database of 28,798 attendees of Biolab Diagnostic Laboratories in Jordan, covering the period from January 19, 2010, to May 26, 2023. Cross-sectional and cohort study analyses were conducted, including estimating HCV antibody (Ab) prevalence, examining associations with HCV Ab positivity, determining the HCV viremic rate, and estimating HCV incidence rate using a retrospective cohort study design. Results: A total of 27,591 individuals, with a median age of 31.3 and 52.9% being females, underwent HCV Ab testing, while 1,450 individuals, with a median age of 42.2 and 32.8% being females, underwent HCV RNA PCR testing. The study sample HCV Ab prevalence was 4.0% (95% CI=3.7-4.2%). After applying probability weights, the weighted HCV Ab prevalence was 5.8% (95% CI=4.6-7.3%). Age was strongly associated with HCV Ab positivity, particularly among individuals aged 50 years or older, who had 10-fold higher odds of being HCV Ab positive compared to those aged 10-19 years. Males had 2.41-fold higher odds of testing positive for HCV Ab compared to females. The HCV viremic rate was 54.1% (95% CI=43.0-65.0%). The cumulative incidence of HCV infection, after 5 years of follow-up, was estimated to be 0.41% (95% CI=0.17-0.99%). The HCV incidence rate was calculated at 1.19 per 1,000 person-years (95% CI=0.50-2.87). Conclusions: Prevalence and incidence of HCV infection were substantial, estimated at 5% and 1 per 1,000 person-years, respectively, and highlighting the presence of core groups actively engaged in the virus' acquisition and transmission. The high observed viremic rate indicates the need for expanding HCV treatment efforts to effectively control HCV transmission in Jordan. Utilizing quality diagnostic laboratories and innovative testing strategies is key to identifying infection carriers and facilitating linkage to care.